Learning Organizational Culture and Firm Performance: The Mediating Effects of Knowledge Creation in Korean Firms. (May 2013) - Song, Ji Hoon; Kolb, Judith A.
The aim of the current research is to examine the relationships between learning culture and performance along with the mediating interaction of knowledge creation. Data for this study were collected from five Korean firms through use of in-house intranet self-response surveys. Responses from 633 manager-level employees were used to identify the relationships among four variables: cultural aspects of the learning organization, four modes of knowledge creation practices, perceived level of knowledge gaining, and perceived level of financial performance. All constructs previously have been identified as related concepts in certain ways; however, no specific and empirically verified structural complex model exists. In this research, first, the influential and causal relations among the variables were examined, and second, a model comparison was conducted between the initially proposed and alternatively proposed structural models. Structural equation modeling and canonical correlation analysis were used for the analyses. The results suggest that the input-related concept of learning culture is not directly related to outcome-related organizational financial improvement but rather has mediating effects through the process-related concept of knowledge creation. Suggestions for future research and implications for human resource development and performance-oriented management are discussed.